2017
DOI: 10.1111/acps.12778
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide DNA methylation analysis in combat veterans reveals a novel locus for PTSD

Abstract: These data highlight the role of DNA methylation as biomarkers of PTSD. The results support the role of previous candidates and uncover novel genes associated with PTSD, such as DOCK2. This study contributes to our understanding of the biological underpinnings of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 83 publications
4
54
0
Order By: Relevance
“…Some of the current human EWAS that have examined mDNA alterations in PTSD are summarized in Table 2. EWAS are listed in chronological order (2010–2017) [54•, 55, 56, 57•, 58, 59•, 60, 61]. The sites with differential mDNA together with the nearest gene are reported.…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…Some of the current human EWAS that have examined mDNA alterations in PTSD are summarized in Table 2. EWAS are listed in chronological order (2010–2017) [54•, 55, 56, 57•, 58, 59•, 60, 61]. The sites with differential mDNA together with the nearest gene are reported.…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…See reference for details. 142 Potentially traumatic events were identified using Criterion A event. The Clinician Administered PTSD Scale for DSM 5 (CAPS-5) was used to assess PTSD over the prior 2 weeks and lifetime by clinical psychologists.…”
Section: Gmrf-qut (Gmfr; Supplementary Table 1 #55)mentioning
confidence: 99%
“…Genetic studies of posttraumatic stress disorder (PTSD) diatheses conducted to date have focused primarily on identifying DNA variants (e.g., single-nucleotide polymorphisms, SNPs) that confer risk for the development of the disorder through candidate gene or genome-wide association studies (GWASs; see, e.g., [1,2]). More recently, studies have also examined differences between PTSD cases and controls in patterns of gene expression [3] and/or DNA methylation (DNAm [4][5][6];). DNAm studies involve measurement of a methyl group on the DNA strand at a cytosine-phosphate-guanine (CpG) site, and when this is present in the promoter region of a gene, DNAm tends to be negatively correlated with the expression of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…First, using a DNAm bead chip that interrogated~27K loci in a sample of 100 subjects from an urban community cohort, Smith et al (2011) reported false discovery rate (FDR)-corrected differences between PTSD cases and controls at loci in 5 genes (ACP5, ANXA2, CLEC9A, TLR8, and TPR) [4]. Second, in a study that used a more comprehensive platform measuring methylation at~850K loci in samples from 96 Australian Vietnam veterans, Mehta et al (2017) found genome-wide significant associations between DNAm and PTSD in four genes (BRSK1, DOCK2, LCN8, and NGF) and in one intergenic locus [5]. Rutten et al (2018) examined pre-to post-deployment changes in DNAm in a cohort of 93 soldiers using a~450K platform and found 17 loci in or near 8 genes that were associated with increasing PTSD symptoms over time [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation